A Zwitterionic, 10 π Aromatic Hemisphere. Issue 45 (12th October 2017) - Hafezi, Nema; Shewa, Wondimagegn T.; Fettinger, James C.; Mascal, Mark
Abstract: A new concept in anionic 10 π aromaticity is described by the embedding of a compensating charge within an aromatic cyclononatetraenide ring by the symmetric superposition of an alkyl ammonium bridge. This is accomplished by the methylation of azatriquinacene to give a quaternary ammonium salt, followed by oxidation to the tetraene and final deprotonation. The resulting zwitterion is a stable [9]annulene with strong aromaticity as shown by its degree of C−C bond equalization and a nucleus‐independent chemical shift value lower than that of benzene. The solid‐state structure shows an eclipsed stacking motif with the electron‐poor ammonium methyl groups occupying the electron‐rich cavity of the aromatic bowl. Abstract : Opposites do more than just attract : An ammonium center is suspended above an anionic, 10 π carbon toroid, leading to a novel, symmetric, bowl‐shaped, strongly aromatic system that, despite being zwitterionic, is hydrocarbon soluble. Internal charge compensation results in unusual stability for an anionic annulene.